Visual Basic 2012 : programmer's reference - Stephens, Rod, 1961- (Wiley, 2012)
This book to cover every and cranny in Visual basic you would need and in - depth understanding of database technologies, custom controls, custom property editors, XML, cryptography, serialization, two - and three - demensional graphics, multi-threading, reflection, the code document object model (DOM), diagnostics, globalization, web services, inter-process communication, work flow, office, ASP, windows forms, WPF, and much more.